Assessment Report, Banso District, Cameroons Province (Colonial Letters and the Contact of Knowledges, 1935)
This file contains colonial memoranda, re-assessment on Banso and continuation notes
Keywords: Archives; Colonisation; Letters; Social norms; Discourse analysis; British Colonisation; Colonial Records; Banso; Southern Cameroons; Postcolonial Heritage; Great Britain; Postcolonial Studies